Production of Waste-Based Lightweight Geopolymer Concretes Using Calcined Bentonite, Fly Ash, Slag, and Expanded Polystyrene Granules - Top, Soner; Nussrat Shukur Shukur, Yasir; Vapur, Hüseyin (Taylor & Francis Inc, 2026)
This study investigates the production of environmentally friendly lightweight geopolymer concretes utilizing fly ash (FA) as the primary precursor with calcined calcium bentonite (CCB), ferrochrome slag (SG), and expanded polystyrene (EPS) as supplementary components. A Box-Behnken design was employed to investigate the combined effects of CCB and SG additions, along with the solid-to-liquid ratio, on the compressive strength. Moderate CCB incorporation, particularly around 10%, improved mechanical performance, achieving strengths above 48 MPa, with a maximum of 51.33 MPa at 90 degrees C for a mix containing 5% CCB and 5% SG. Higher CCB dosages (>20%) reduced strength due to matrix dilution, while SG showed limited contribution at elevated levels. Incorporation of EPS granules reduced density to as low as 1292 kg/m & sup3;, yet compressive strengths between 25 and 30 MPa were maintained in mixes with 10% CCB and 0.3% EPS. SEM-EDX analysis confirmed dense geopolymer matrices in FA-CCB composites, whereas SG particles appeared less integrated. These results confirm the potential for producing high-strength, lightweight geopolymer concretes through the effective valorization of waste. The combined use of FA, CCB, SG, and EPS offers a sustainable pathway for resource-efficient construction that supports circular resource utilization.
Keywords: Geopolymer; Calcined Calcium Bentonite; Fly Ash; Slag; Lightweight; Polystyrene Granules